Anxiety Regarding COVID-19 Is Related to Attentional Control: The Mediating Role of Anxiety Sensitivity - Guo, Yawen; Yang, Haibo; Elhai, Jon; McKay, Dean (Frontiers in Psychiatry, 2021)
Background: As an emergent public health event, COVID-19 has had a significant impact on mental health, particularly causing anxiety. Some cognitive-affective related studies have demonstrated that attentional control is related to levels of anxiety. More specifically, recent research has shown that anxiety sensitivity is uniquely associated with mental health responses to COVID-19. The aim of the current study was to investigate the role of anxiety sensitivity during COVID-19 outbreak period, especially physical and cognitive concerns, in relation to attentional control and anxiety. Methods: It is a questionnaire study. A total of 464 participants were recruited through online sampling between February and March, 2020. They were surveyed by the Attentional Control Scale (ATTC), Anxiety Sensitivity Index-3 (ASI-3) and Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using descriptive statistics and correlation analysis. We also tested the mediating effect. Results: The results showed that attentional control is negatively correlated with physical concern, cognitive concern and anxiety. And results support that physical and cognitive concerns play a mediating role between attentional control and anxiety. Conclusions: Anxiety sensitivity plays a mediating role between attentional control and anxiety. These findings can help effective prevention and intervention of anxiety.